2000
DOI: 10.1101/lm.33000
|View full text |Cite
|
Sign up to set email alerts
|

Fornix and Hippocampal Atrophy in Traumatic Brain Injury

Abstract: This study compared a fornix cross-sectional-area measurement and hippocampal volume in 86 traumatic brain injury (TBI) subjects with 46 normal controls. The TBI group showed a significant reduction in fornix area and hippocampal volume. It was also shown that initial injury severity was related to the degree of atrophy in both structures. Although fornix size and hippocampal volume correlated, such a modest correlation between these two structures suggests differential and potentially independent mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(96 citation statements)
references
References 26 publications
7
88
0
1
Order By: Relevance
“…Further, longitudinal results indicate that both of these effects emerge relatively early after injury, with hypersynchrony progressing from a uni-to a bilateral phenomenon. These findings fit with previous literature documenting structural hippocampal anomalies 77,78 and episodic memory impairment 79-81 after brain trauma. Critically, our results show that the connectivity profiles of the hippocampi do not seem to ''recover'' with greater time postinjury.…”
Section: Development Of Hippocampal Connectivity Alterationssupporting
confidence: 82%
“…Further, longitudinal results indicate that both of these effects emerge relatively early after injury, with hypersynchrony progressing from a uni-to a bilateral phenomenon. These findings fit with previous literature documenting structural hippocampal anomalies 77,78 and episodic memory impairment 79-81 after brain trauma. Critically, our results show that the connectivity profiles of the hippocampi do not seem to ''recover'' with greater time postinjury.…”
Section: Development Of Hippocampal Connectivity Alterationssupporting
confidence: 82%
“…Blumbergs et al (1995) in a follow-up study demonstrated that the microscopic pathology was on a continuum from mild (GCS of 13-15) to severe (GCS of 3-8), again demonstrating the susceptibility of the fornix. As shown by Viano et al (2005b), the fornix is distinctly vulnerable to the stress0strain effects of concussion and is a common area of damage in moderate-to-severe TBI, as visualized using MRI (Gale et al, 1995;Tate & Bigler, 2000;Tomaiuolo et al, 2004), where the degree of atrophy is related to severity of injury Tate & Bigler, 2000;Tomaiuolo et al, 2004;Wilde et al, 2006b). Because the fornix is a white matter structure containing projecting axons from the hippocampus, disruption in fornix integrity likely relates to the concussive effects of disrupted short-term memory, at least transiently.…”
Section: Is Brain Injury On a Continuum: Concussion R Severe Tbi?mentioning
confidence: 99%
“…Volumetric magnetic resonance imaging (MRI) studies of chronic TBI (Sidaros et al, 2009;Trivedi et al, 2007;Levin et al, 2000;Tate and Bigler, 2000;Verger et al, 2001;Yount et al, 2002) have reported that global and regional brain atrophy occurs over a period ranging from months to years after the injury. This atrophy seems to be dependent on the extent of the initial injury, can involve important structures such as the hippocampus, and correlates with deficits in long-term cognitive performance (Wilde et al, 2005;Levine et al, 2008).…”
Section: Introductionmentioning
confidence: 99%